A Valence Tautomeric Dinuclear Copper Tetrakisguanidine Complex. Issue 30 (16th June 2016) - Wiesner, Sven; Wagner, Arne; Kaifer, Elisabeth; Himmel, Hans‐Jörg
Abstract: We report on the first valence tautomeric dinuclear copper complex, featuring 2, 3, 5, 6‐tetrakis(tetramethylguanidino)pyridine as a bridging redox‐active GFA (guanidino‐functionalized aromatic) ligand. The preferred electronic structure of the complex is massively influenced by the environment. In the solid state and in nonpolar solvents a paramagnetic, dinuclear Cu II complex with a neutral GFA ligand is present. In polar solvents, the electronic structure changes to a diamagnetic, dinuclear Cu I complex with a twofold‐oxidized GFA ligand. Using acetone as a solvent, both electronic structures are accessible due to a temperature‐dependent equilibrium between the two valence tautomeric complexes. Our results pave the way for a broader use of valence tautomeric transition‐metal complexes in catalytic reactions since anionic coligands can now be tolerated owing to the neutral/positively charged GFA ligand. Abstract : Let's switch ! By varying the temperature, it is possible to switch between a red diamagnetic copper(I) complex and a green paramagnetic copper(II) complex based on the phenomenon of valence tautomerism. This first example of a valence‐tautomeric guanidine complex consists of two copper centers that are bridged by a redox‐active, guanidino‐functionalized aromatic ligand (see figure).